Soft tap water urgently needed for reducing risks of kidney stones at the rural villages in Yangxin, a poverty-alleviated county in central China - Zhao, Jiaxin; Wang, Mingyao; Jiang, Tan; Wang, Fangsi; Shi, Xinyue; Zhang, Yun; Xu, Kun (Frontiers in Water, 2024)
IntroductionClean drinking water is a necessity for maintaining public health and livelihoods. Hard water containing excessive calcium and magnesium threatens urinary health with elevated risks of kidney stones at rural villages with tap water shortages. After entitled poverty alleviation in 2019, residents of Yangxin county of Hubei Province in central China unexpected suffered shortage of tap water and additional cost of water softening. However, the impact of lack of tap water on risks of kidney stones was not yet quantified for residents at rural villages in Yangxin.MethodsWe conducted a cross-sectional analysis by testing 216 water samples from 114 families at four villages and surveying urinary health and living conditions of each householder.ResultsLab tests showed that mean total hardness of well and tap water at each village was above 355 mg/L CaCO3, except tap water from the village with government support for industrial development. Mean softening depth was 309.3 mg/L at the families paying for filters or bottle water, and mean annual cost of water was 1,915 CNY (1 CNY = 0.14 USD) equivalent to 5.8% of mean annual household income. Mean tap water availability was only 34%, and the prevalence of kidney stones among the four villages was 33.9%, 25.0% higher than the rate of kidney stones in Hubei Province. About 60% of the families showed strong willingness to accept annual government compensation of 3,324 CNY for clean water supply, whereas only 2.6% of the families wanted to pay government for water treatment. Using logistic and random forest regression models, we identify factors associated with the prevalence of kidney stones as gender (males have 3.78 times the risks of females), age (2.42 times greater risks if 10 years older), body mass index (higher risks if overweight or obese), total hardness of drinking water (2.59 times for a 100 mg/L increase in total hardness), and tap water availability (2.42 times higher among those without tap water supply compared to those with constant supply).DiscussionOld and obese males are more likely to be diagnosed with kidney stones, but tap water shortages and high total hardness of drinking water increase the risks for all residents. To improve urinary health and meet support needs of residents, tap water supply of soft water is urgently needed at the rural villages in Yangxin.